Effectiveness of sheet pile enclosure with drainage ability as liquefaction countermeasure for river levees - Mitsu Okamura; Mizuki Suyama; Kohei Ono (Soils and Foundations)
Sheet-pile enclosures are often employed as liquefaction countermeasures for river levees in Japan. However, the stiffness of the sheet piles alone is often insufficient to maintain levees on liquefied foundation soil high enough to prevent overflooding. Sheet piles with additional members having drainage ability have been developed and employed, which are expected to provide the combined effects of lateral confinement and dissipation of excess pore pressure from the liquefiable soil beneath the levees. In this study, a series of centrifuge tests was conducted to assess the liquefaction-induced settlement of levees and the excess pore pressure generated in sand beds enclosed by sheet piles with and without drainage ability. The effects of the drainage ability were studied for liquefiable foundation soil with a wide range of permeabilities. The results confirmed that the settlement in a sand bed is closely related to the excess pore pressure. Additionally, a practical method was developed for predicting excess pore pressure and then validated through a comparison with test observations. Using this procedure, the effects of the sand-bed geometry, levee height, and severity of the earthquake shaking were studied in relation to the characteristics of the resistance of the sand to liquefaction on the excess pore pressure. Moreover, the applicability of drainage members to a Japanese river levee countermeasure project was analyzed. For practical use in river levee rehabilitation projects, drainage members were confirmed to be more effective for sand with a higher liquefaction-resistance. Owing to the high maximum acceleration of ground motions stipulated in the design code, these drainage members may not be effective for sand with permeabilities in the order of 10−5 m/s or lower. In addition, the slopes of the liquefaction resistance curves of the sand were observed to significantly affect the effectiveness of the drainage members. Therefore, the liquefaction-resistance curves are considered to be more important than the liquefaction-resistance ratio alone when designing drainage members as a liquefaction countermeasure.